Profile of Cerebral Palsy Patients in Dr. Soetomo General Hospital Surabaya, Indonesia - Qorina Nadya Salfi; Darto Saharso; Atika Atika (Biomolecular and Health Science Journal, 2019)
Introduction: Limited profile data of Cerebral Palsy (CP) patients in Indonesia leads CP to be a less-known disease. The aim of this study is to describe CP patient’s characteristics, including demographic aspect, gestation and birth history, and CP related condition in Dr. Soetomo General Hospital Surabaya, Indonesia.Methods: Cross-sectional study using medical records of CP patients in Dr. Soetomo General Hospital (Surabaya, Indonesia) Outpatient Installation for Pediatric Neurology from January 2016 to June 2018. Data processed descriptively.Results: From total 107 patients, 50 subjects met inclusion criteria. Mean age was 6.16 years old, with domination of male (3:2), live in Surabaya (56%), malnourished (24%), normal birth weight (80.9%), term age of birth (66.7%), spontaneous labor (60%), and also prenatal events as causes of Cerebral Palsy (69.5%). Pneumonia was found to be most among postnatal events leading to Cerebral Palsy (30%). Most of the type was spastic (9:1) with quadriplegic as the dominating one (64%). Congenital malformation was rarely found (38%), but co-morbidities were found in almost all sample (92%).Conclusion: Gestation and birth history of CP patients are mostly ranged normal. Prenatal etiology is found dominating as the cause of CP, therefore emendation in antenatal care (ANC) shall be considered. Analytical study about CP in Indonesia also must be improved because it is still hardly found.